Total Quality Management (Tqm): Konsep Dan Prinsip Dalam Pendidikan Islam - Singgih Aji Purnomo; Maksum Maksum (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2020)
The face of Islamic education in the Indonesian State lately looks interesting. This can be seen from the management pattern of educational institutions in the midst of the Coronavirus disease (COVID-19) pandemic. The school principal does everything possible so that the education process runs well and is of good quality. Schools as educational institutions are noble industrial institutions with two important missions, namely profit and society. To achieve this mission, a management pattern is needed. Total Quality Management (TQM) is important, because the process of continuous and comprehensive improvement is in it. This paper uses a literature research method which is discussed in the form of argumentation and descriptive narrative. This literature study shows that to achieve the best quality, all components of educational institutions are encouraged to act together (as a whole) in managing the educational institution.